Induction of tolerance to salt stress in soursop seedlings using hydrogen peroxide - da Silva, André Alisson Rodrigues; de Lima, Geovani Soares; Vieira de Azevedo, Carlos Alberto; de Sá Almeida Veloso, Luana Lucas; Capitulino, Jessica Dayanne; Gheyi, Hans Raj (Comunicata Scientiae, 2019)
The exogenous use of hydrogen peroxide is an alternative in the acclimatization of plants to salt stress due to the greater activity of antioxidant enzymes. In this perspective, this study aimed to evaluate the gas exchange and the growth of soursop seedlings under salt stress using hydrogen peroxide. The study was conducted under greenhouse conditions. The treatments were distributed in randomized blocks, in a 5 x 2 factorial arrangement, related to five levels of electrical conductivity of the irrigation water - ECw (0.6, 1.2, 1.8, 2.4, and 3.0 dS m-1) and two concentrations of hydrogen peroxide - H2O2 (0 and 20 μM), with four replicates and two plants per plot. The effects of the treatments were evaluated by the variables of gas exchange and growth. The increase in water salinity negatively affected the gas exchange and the growth of the soursop seedlings. The gas exchange and growth variables presented deleterious effects caused by the salinity of the irrigation water, mitigated by the exogenous application of hydrogen peroxide at the concentration of 20 μM. The exogenous use of hydrogen peroxide at the concentration of 20 μM can be used to induce salt tolerance in soursop seedlings.